Effect of Salicylic Acid on Antioxidant Activity in Milk Thistle Hairy Root Cultures - M Khalili; T Hasanloo; SK Kazemi Tabar; R Sepehrifar (Institue of Medicinal Plants, ACECR, 2010)
Background: Elicitors can trigger defense responses and activate specific genes involved in secondary metabolite biosynthesis. Objective: For understanding SA-treatment signaling pathway we determined defense-related compounds and enzymes in S. marianum hairy root cultures. Methods: 28 day old hairy roots were treated by salicylic acid (6 mg/50 ml culture) for different times (24, 48, 72, 96 and 120 h). The antioxidant activity was assayed by the 1-diphenyl-2-picrylhydrazyl stable free radical method and results were calculated based on the IC50. H2O2, peroxidase and ascorbate peroxidase activity and total tocopherol content was measured in treated and non-treated hairy root cultures. Results: The highest accumulation of H2O2 was 86.60 µmol g-1 DW that was obtained 120 h after elicitation (2-times of non-treated hairy roots). IC50 increased upon treatment and was 1.15- times higher than the control 24h after elicitation. The content of total tocopherol content under SA treatment was lower than the control experiments. Maximum activity of peroxidase and ascorbate peroxidase were 0.17 and 1.50 μmol min-1 mg-1 protein, 96 and 72 h after elicitation, respectively. Conclusion: Oxidative stress defends system can be activated by salicylic acid in Silybum marianum hairy root cultures. This study suggested that exogenous SA can increase H2O2 content of hairy roots, and induce the expression of antioxidant enzymes and increase secondary metabolite accumulation.